Ethical business practices in managing tourism in Cibodas Village as a tourist destination - Pangarso, Astadi; Susanty, Ade Irma; Wulansari, Puspita (Society : Jurnal Pengabdian Masyarakat, 2025)
This community service program helped tourism managers in Cibodas Village, a growing tourist destination in Pasirjambu, Bandung, learn more about how to run a business ethically. Some of the main problems were a lack of openness, poor professional administration, and a lack of youth involvement. The initiative set up training sessions that included case studies from other villages, interactive conversations, and lessons on ethical business practices to help people come up with solutions that worked for their area. The results showed that people were more aware of ethical standards, that stakeholders worked together better, and that they were committed to managing tourism in a way that respects cultural heritage and the environment.